1987
DOI: 10.1002/cne.902590403
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine tegmental nucleus of the rat: Cytoarchitecture, cytochemistry, and some extrapyramidal connections of the mesopontine tegmentum

Abstract: The pedunculopontine tegmental nucleus (PPTn) was originally defined on cytoarchitectonic grounds in humans. We have employed cytoarchitectonic, cytochemical, and connectional criteria to define a homologous cell group in the rat. A detailed cytoarchitectonic delineation of the mesopontine tegmentum, including the PPTn, was performed employing tissue stained for Nissl substance. Choline acetyltransferase (ChAT) immunostained tissue was then analyzed in order to investigate the relationship of cholinergic perik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
259
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(286 citation statements)
references
References 134 publications
24
259
2
1
Order By: Relevance
“…Postictal states can be compared to movement arrest, using similar suppressive mechanisms during motor seizure termination. Decreased uptake in the PPTg is consistent with lack of inhibitory GABAergic regulation, e.g., from the SNR, which represents one of most important afferent projections of the PPTg (Rye et al, 1987;Spann and Grofova, 1991). This in turn results in an increase of cholinergic or glutamatergic activity within the PPTg, which is reflected by increased activity in the STN, one of the main ascending projections of PPTg (Nakano et al, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…Postictal states can be compared to movement arrest, using similar suppressive mechanisms during motor seizure termination. Decreased uptake in the PPTg is consistent with lack of inhibitory GABAergic regulation, e.g., from the SNR, which represents one of most important afferent projections of the PPTg (Rye et al, 1987;Spann and Grofova, 1991). This in turn results in an increase of cholinergic or glutamatergic activity within the PPTg, which is reflected by increased activity in the STN, one of the main ascending projections of PPTg (Nakano et al, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…The PPN is a very heterogeneous structure, consisting of a caudolateral pars compacta (PPNc) and an anteromedial pars dissipata. Cholinergic cells predominate in PPNc, but PPNc and anteromedial pars dissipata also contain large populations of GABAergic or glutamatergic neurons [77][78][79]. The input and output relationships of the various neuron groups in the PPN have not been precisely determined, but it is known that the nucleus gives rise to projections to the basal ganglia, thalamus, basal forebrain, reticular formation, and spinal cord [69,74,[80][81][82][83][84][85][86][87][88][89][90][91][92][93], thus being, at the same time, part of the extended basal ganglia family of nuclei [74], and a conduit of descending basal ganglia outputs.…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%
“…The reciprocal connections existing between the PPTg and the basal ganglia have been extensively studied (Saper and Loewy 1982;Jackson and Crossman 1983;Rye et al 1987;Lee et al 1988), with emphasis on their relationship with the SN (Beninato and Spencer 1987;Clarke et al 1987;Scarnati et al 1987b;Beninato and Spencer 1988;Gould et al 1989;Spann and Grofova 1991;Lavoie and Parent 1994). The pedunculonigral projection may be an indirect way of modulating striatal activity, as PPTg nigral afferents synapse onto dopaminergic nigrostriatal neurons (Tokuno et al 1988;Bolam et al 1991;Hern谩ndez-L贸pez et al 1992).…”
Section: Thalamic Territories Of Overlapmentioning
confidence: 99%
“…The most caudal brain nucleus receiving projections from the basal ganglia is the pedunculopontine tegmental nucleus (PPTg). Anterograde and retrograde tract-tracing procedures and neurophysiological studies have reported the existence of a close and reciprocal relationship between the PPTg and several basal ganglia structures such as the entopeduncular nucleus (EP), the subthalamic nucleus (STh) and the substantia nigra (SN) (Saper and Loewy 1982;Jackson and Crossman 1983;Scarnati et al 1987a;Rye et al 1987;Spann and Grofova 1989;Lavoie et al 1990;Lavoie and Parent 1994a). Basal ganglia structures lack direct access to pontomedullary or spinal nuclei and the PPTg has therefore been considered a link between the basal ganglia and the brainstem and spinal cord.…”
Section: Introductionmentioning
confidence: 99%